Cumulative stressors reduce the self‐regulating capacity of coastal ecosystems. Issue 1 (29th October 2020) - Thrush, Simon F.; Hewitt, Judi E.; Gladstone‐Gallagher, Rebecca V.; Savage, Candida; Lundquist, Carolyn; O'Meara, Teri; Vieillard, Amanda; Hillman, Jenny R.; Mangan, Stephanie; Douglas, Emily J.; Clark, Dana E.; Lohrer, Andrew M.; et al.
Abstract: Marine ecosystems are prone to tipping points, particularly in coastal zones where dramatic changes are associated with interactions between cumulative stressors (e.g., shellfish harvesting, eutrophication and sediment inputs) and ecosystem functions. A common feature of many degraded estuaries is elevated turbidity that reduces incident light to the seafloor, resulting from multiple factors including changes in sediment loading, sea‐level rise and increased water column algal biomass. To determine whether cumulative effects of elevated turbidity may result in marked changes in the interactions between ecosystem components driving nutrient processing, we conducted a large‐scale experiment manipulating sediment nitrogen concentrations in 15 estuaries across a national‐scale gradient in incident light at the seafloor. We identified a threshold in incident light that was related to distinct changes in the ecosystem interaction networks (EIN) that drive nutrient processing. Above this threshold, network connectivity was high with clear mechanistic links to denitrification and the role of large shellfish in nitrogen processing. The EIN analyses revealed interacting stressors resulting in a decoupling of ecosystem processes in turbid estuaries with a lower capacity to denitrify and process nitrogen. This suggests that, as turbidity increases with sediment load, coastal areas can be more vulnerable to eutrophication. The identified interactions between light, nutrient processing and the abundance of large shellfish emphasizes the importance of actions that seek to manage multiple stressors and conserve or enhance shellfish abundance, rather than actions focusing on limiting a single stressor.